Moral Cognition and the Law and Ethics of Armed Conflict. Issue 4 (2nd December 2015) - Traven, David
Abstract: In contemporary political science, many believe that normative restrictions on armed conflict are an outgrowth of Western culture and the just war tradition. Drawing on historical evidence, which shows that political actors in Ancient China and the early Islamic empire endorsed civilian protection rules, I claim that such norms are more common than most International Relations (IR) theorists suppose. For IR theory, this raises an important puzzle: How can we explain why similar normative ideas emerged in human societies that are otherwise very different? Building on research in cognitive science, social psychology, and social neuroscience, I argue that most people have natural cognitive and emotional predispositions that bias the emergence and transmission of cultural norms that protect non-combatants. More specifically, capacities for perspective-taking and empathy shape how people interpret the limits of their moral commitments, and when these capacities are engaged, intuitional heuristics affect how they judge the morality of killing in war. What is more, I claim that three key contextual variables moderate the connection between innate moral intuitions and the development of civilian protection norms: (i) societal interdependence, (ii) the social empowerment of marginal actors, and (iii) the creation of norms in argumentative contexts that require impartial moral reasoning. I argue that rationalist and constructivist theories of norm emergence will be able to better explain the emergence, the durability, and the institutional design of the norms of war by incorporating this naturalistic theory of moral cognition.